Distraction of Symbolic Behavior in Regular Classrooms - Billinger, Stefan (Frontiers in Psychology, 2012)
The purpose of the present study is to develop more precise methods to explore the interaction between contextual factors in teacher instructions in regular classroom settings and students’ abilities to use symbolic information in the instruction. The ability to easily show symbolic behavior could be expected to influence student’s capacity to be active and participate. The present study examines distraction in students’ shifts from the use of “non-symbolic” to “symbolic” behavior in regular classroom settings. The 53 students (29 boys and 24 girls), ages 11 to 13 years old, who participated in the study were from three classes in the same Swedish compulsory regular school. Based on their test performances in a previous study, 25 students (47%) were defined as showing symbolic behavior (symbolic), and 28 students (53%) as not showing it (non-symbolic). In the present study, new post training test trials with distractors were added. Students from both the symbolic and non-symbolic groups scored significantly fewer correct answers on the post-training test trials with distraction stimuli (p. < .05) than in post-training test trials without distraction. In the post-training test trials with competing arbitrary distractors, both groups were distracted significantly more than in the post-training test trials with competing non-arbitrary distractors (p. < .05). The results indicate that a relatively easily administered and socially acceptable procedure seems to give observational data about variations in students’ symbolic behavior in relation to contextual factors in regular classroom. The main conclusion to be drawn from the results is that the observational procedure used in this study seems to have a potential to be used to explore the interaction between contextual factors and more complex student behavior such as cognition and the pragmatic use of language in regular classroom.